Aligning Omani legislation with the principles of good governance: an integrated vision between the Islamic perspective and international standards - Al-Farsi, Ahmed Mahmood Hamdan; Muhammad Nazir Alias,; Razaleigh Muhamat @ Kawangit, (Pusat Penyelidikan Syariah, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2024)
The Sultanate of Oman seeks to solidify the principles of good governance in state administration, drawing upon Islamic values and international standards. The Basic Statute of the State enshrines these principles, such as the rule of law, justice, and participation. However, practical challenges persist, including irregular alignment of laws with the constitution, limited legislative authority of the Council of Oman, insufficient legal protection for whistleblowers, and a lack of national-level good governance indicators aligned with international standards. This study aims to evaluate the extent to which Omani legislation and institutions align with the principles of good governance from both Islamic and international perspectives, identifying gaps that need to be addressed to strengthen governance frameworks in the country. The study employs content analysis of the Basic Statute of the State and key legislation, such as the Law of the Council of Oman and the Financial and Administrative Control Law, alongside an examination of the roles of relevant institutions, including the Council of Oman and oversight bodies. The findings indicate that Oman's legislative and institutional framework generally aligns with the essentials of good governance but reveals certain deficiencies requiring improvement. These include irregular alignment of laws with the constitution, limited government responsiveness to the Council’s legislative proposals, and weak coordination among oversight bodies. The study recommends constitutional reforms to enhance legislative alignment, expansion of the Council of Oman’s powers, enactment of a whistleblower protection law, establishment of a national anti- corruption body, promotion of transparency and inter-agency collaboration, and inclusion of civil society organizations in policymaking. Additionally, it calls for the development and dissemination of national good governance indicators. These recommendations are aligned with global best practices and Islamic values, supporting Oman’s ongoing efforts to enhance institutional governance as part of its Vision 2040.